Antara Produktivitas dan Kemanusiaan: Analisis Komparatif Budaya Kerja High Work Intensity dan Work-Life Balance dalam Perspektif Manajemen Sumber Daya Insani - Neng Nina Nuraeni; Ahyakudin A (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to conduct a comparative analysis of two work culture models that have emerged in contemporary organizational dynamics: high work intensity (HWI) and work-life balance (WLB), from the perspective of Human Resource Management (HRM). Using the Systematic Literature Review (SLR) method, this study analyzed 18 scientific sources indexed in SINTA and Scopus published between 2019 and 2025. The findings indicate that while HWI can drive significant short-term productivity, this model is prone to causing burnout, declining mental health, and high employee turnover rates in the long term. Conversely, WLB has proven more effective in fostering loyalty, creativity, and sustainable HR performance. Furthermore, this article highlights the perspective of humanistic values in HRM, which positions employees not merely as factors of production but as dignified individuals who must be protected. A review of the maqashid al-sharia, particularly the principle of hifzun nafs (preserving life and health), reinforces the argument that work models that disregard employee well-being contradict the fundamental values of civilized human resource management. This study concludes that the ideal model is not a choice between two opposing poles, but rather a synthesis in the form of a strong work ethic that remains grounded in human values.